Association of Chronic Obstructive Pulmonary Disease with Risk of Psychiatric Disorders: A Two-Sample Mendelian Randomization Study - Zhang Q; Zhang H; Xu Q (International Journal of COPD, 2024)
Qinxia Zhang,1,* Haifu Zhang,2,* Qinxing Xu1 1Department of Respiratory Medicine, The First People’s Hospital of Fuyang, Hangzhou, Zhejiang, 311400, People’s Republic of China; 2Department of Medicine, The First People’s Hospital of Fuyang, Hangzhou, Zhejiang, 311400, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qinxing Xu, Department of Respiratory Medicine, The First People’s Hospital of Fuyang, Hangzhou, Zhejiang, 311400, People’s Republic of China, Email xuqinxing@yeah.netBackground: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory disorder often accompanied by comorbidities. Although the past few years have witnessed significant scientific progress, the potential relationship between COPD and mental illness remains a subject of debate.Materials and Methods: We retrieved COPD data from the genome-wide association studies (GWAS) directory and data on mental illnesses, including Alzheimer’s disease, schizophrenia, panic disorder, attention deficit hyperactivity disorder (ADHD), bipolar disorder, major depressive disorder, multiple disabilities, obsessive-compulsive disorder, post-traumatic stress disorder, and schizophrenia, from the Psychiatric Genomics Consortium. A two-sample Mendelian randomization (MR) approach was applied to explore the association between COPD and mental illnesses, with subgroup analyses based on smoking history.Results: Our two-sample MR analysis revealed no causal link between overall COPD and the development of common psychiatric disorders. Subgroup analyses based on smoking history showed no causal association between never-smokers with COPD and the occurrence of psychiatric disorders. However, ever-smokers with COPD were associated with a significantly increased risk of ADHD (OR: 2.303, 95% CI: 1.558– 3.403, P = 0.001) and a modestly reduced risk of Alzheimer’s disease (OR: 0.994, 95% CI: 0.988– 0.999, P = 0.034).Conclusion: COPD patients with a history of smoking face a higher risk of developing ADHD but may experience a slight reduction in the risk of Alzheimer’s disease. Conversely, there was no observed causal association between COPD and psychiatric disorders among patients who never smoked.Keywords: chronic obstructive pulmonary disease, psychiatric disorders, Mendelian randomization